RESPON PEMBERIAN DOSIS PUPUK NPK DAN PUPUK KASCING TERHADAP PERTUMBUHAN DAN HASIL KACANG MERAH (Phaseolus vulgaris L.) - Mulyono, Mulyono; Rahmi, Faidha; Pinteni Arafah, Ipak (Cangkok, 2023)
This study aims to determine the response of giving doses of NPK fertilizer and vermicompost fertilizer, and to determine their interactions on the growth and yield of red bean plants (Phaseolus vulgaris L.). This study used a Randomized Group Design (RAK) factorial pattern consisting of 2 treatment factors, there were 9 treatment combinations with 3 replications so that the number of experiments was 27 experimental plots. The distance between plots was 50 cm with a spacing of 30 cm x 20 cm, BASF 16 16 16 NPK fertilizer dose consisting of 3 treatments, namely: N1 : 50 grams/plot, N2: 100 grams/plot, N3: 150 grams/plot Doses of vermicompost fertilizer consisting of 3 treatments, namely: K1 : 175 grams/plot, K2: 225 grams/plot, K3: 275 grams/plot. The treatment of NPK fertilizer doses had a significant effect on plant height at 20 and 30 HST, but had a very significant effect on plant height at 40 HST, number of leaves, number of pods, seed weight per-sample and seed weight per-plot. The treatment of N2 (100 grams/plot) showed the best treatment. The dose of fertilizer treatment did not significantly affect all parameters. There was no significant interaction between the doses of NPK fertilizer and vermicompost fertilizer on the growth and yield of kidney beans.